Detection of undiagnosed diabetes using UK general practice data - Holt, T (2008)
An estimated 750,000 people in the UK have diabetes that is either undiagnosed or unrecorded on diabetes registers. Opportunities are missed to prevent or delay complications and reduce cardiovascular risk. This 'missing population' problem has been addressed at various levels raising awareness among the public; targeted case finding in at-risk groups; and lowering the threshold for investigation of suggestive symptoms among clinicians. Cardiovascular risk assessments are recommended in the UK for the over 40-year-old population and include blood glucose measurements. To further support these measures, this article discusses a recently reported technique for identifying possible cases of undiagnosed diabetes using simple searches on primary care databases, and its implications for practice and future research. © SAGE Publications 2008 Los Angeles, London, New Delhi and Singapore.